2017
DOI: 10.1371/journal.pgen.1006778
|View full text |Cite
|
Sign up to set email alerts
|

Gene duplication and co-evolution of G1/S transcription factor specificity in fungi are essential for optimizing cell fitness

Abstract: Transcriptional regulatory networks play a central role in optimizing cell survival. How DNA binding domains and cis-regulatory DNA binding sequences have co-evolved to allow the expansion of transcriptional networks and how this contributes to cellular fitness remains unclear. Here we experimentally explore how the complex G1/S transcriptional network evolved in the budding yeast Saccharomyces cerevisiae by examining different chimeric transcription factor (TF) complexes. Over 200 G1/S genes are regulated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Our mathematical model of the Start transition extends previous models based solely on the relief of SBF/MBF inhibition by Cln-Cdc28-mediated phosphorylation and Whi5 nuclear export (Cross et al, 2002;Di Talia et al, 2009;Huang et al, 2009;Wang et al, 2009;Charvin et al, 2010;Adames et al, 2015;Liu et al, 2015;Laomettachit et al, 2016;Palumbo et al, 2016;Aldea et al, 2017) by incorporating SBF/MBF accumulation as cells grow in G1 phase and the enhanced expression of SBF/MBF in poor nutrients. Our model thus accommodates specialized functions of SBF and MBF (Hendler et al, 2017), unlike prior models that treat SBF and MBF activity as a single parameter (Laomettachit et al, 2016). We also find that Cln2 amplification is damped due to an increased contribution from MBF in glycerol medium.…”
Section: Discussionmentioning
confidence: 87%
“…Our mathematical model of the Start transition extends previous models based solely on the relief of SBF/MBF inhibition by Cln-Cdc28-mediated phosphorylation and Whi5 nuclear export (Cross et al, 2002;Di Talia et al, 2009;Huang et al, 2009;Wang et al, 2009;Charvin et al, 2010;Adames et al, 2015;Liu et al, 2015;Laomettachit et al, 2016;Palumbo et al, 2016;Aldea et al, 2017) by incorporating SBF/MBF accumulation as cells grow in G1 phase and the enhanced expression of SBF/MBF in poor nutrients. Our model thus accommodates specialized functions of SBF and MBF (Hendler et al, 2017), unlike prior models that treat SBF and MBF activity as a single parameter (Laomettachit et al, 2016). We also find that Cln2 amplification is damped due to an increased contribution from MBF in glycerol medium.…”
Section: Discussionmentioning
confidence: 87%
“…Further support for the functional division of the SBF regulon to "modern" genes containing SCB motifs and "ancient" genes containing MCB motifs came from chromatin immunoprecipitation (ChIP) experiments. We found that Sc Swi4 exhibits much higher affinity for the SCB motif relative to the MCB-like motif while the chimeric TFs containing distantly related DBDs can only bind the MCB-like motif (Hendler, et al 2017). These results suggest that the Sc Swi4 evolved for optimized binding to the SCB motif to enable normal cell growth and morphogenesis.…”
Section: New Insights Regarding Mbf and Sbf Evolutionmentioning
confidence: 84%
“…Despite extensive studies in different organisms, relatively little was known regarding how Swi4 and Mbp1 DNA binding domains (DBDs) co-evolved to recognize the SCB and MCB DNA binding sequences, respectively, to synchronize the expression of a large set of genes during the G1 to S transition. To address these questions, we recently generated and examined the function of different chimeric Mbp1 and Swi4 TFs in Sc (Hendler, et al 2017). Specifically, we generated to slow growth rate and severe morphological defects upon cell growth, budding and division (Hendler, et al 2017).…”
Section: New Insights Regarding Mbf and Sbf Evolutionmentioning
confidence: 99%
See 2 more Smart Citations